Recent progress in maize lethal necrosis disease: From pathogens to integrated pest management - Bin-hui ZHAN; Xiu-ling YANG; Steven A. LOMMEL; Xue-ping ZHOU (Journal of Integrative Agriculture, 2022)
Maize (Zea mays), as a staple food and an important industrial raw material, has been widely cultivated for centuries especially by smallholder farmers. Maize lethal necrosis disease (MLND) is a serious disease infecting maize, which caused devastating damage in the African region recently. MLND is induced by co-infection of maize chlorotic mottle virus and one of several cereal-infecting viruses in the Potyviridae family, with the symptoms ranging from chlorotic mottle to plant death at different infection stages. Integrated pest management for MLND needs strengthening detection, focusing on prevention and effective control. Early detection system of MLND has been successfully established by serological methods, nucleic acid-based methods, next-generation sequencing, etc. The practices, such as using certified seeds, sanitary measures, crop rotation, tolerant or resistant varieties etc., have been considered as the effective, economical and eco-friendly way to prevent and control MLND.